Research Paper DESIGN, OPTIMIZATION AND EVALUATION OF EMPAGLIFLOZIN ORODISPERSIBLE TABLETS USING DIFFERENT SUPERDISINTEGRANTS - DWIVEDI, AKANKSHA; DARWHEKAR, G. N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The objective of this study was to formulate orodispersible tablets containing empagliflozin by direct compression method with sufficient hardness and rapid disintegration time and to study the effect of functionality differences of super-disintegrants on the tablet properties. Methods: A two factor three level factorial design (32) was used for the formulation optimization of orodispersible tablets of Empagliflozin and experimental trials were performed on all possible formulations, in which the amount of β-cyclodextrin, crospovidone and croscarmellose sodium were selected as independent variables (factor) varied at three different levels: low (-1), medium (0), and high (+1) levels. The drug release and disintegration time were used as dependent variables (response). All formulations were characterized for parameters such as diameter, hardness, weight, thickness, friability, disintegration time, drug release. Results: Formulation FD6 having 30 sec disintegration time, 98.84% drug release after 30 min, 2.8 kg/cm2 hardness and 0.292% friability was found best among all formulations and selected as an optimized formulation with rapid onset of action and enhanced bioavailability (more than 98% drug release within 30 min.) as compared to the oral empagliflozin tablet. Conclusion: Empagliflozin orodispersible tablets with different superdisintegrants were successfully prepared and formulation containing highest percentage of crospovidone was found best among all other formulations in terms of bioavailability and rapid onset of action.